2018
DOI: 10.1016/j.heliyon.2018.e00975
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic diet increases mitochondria volume in the liver and skeletal muscle without altering oxidative stress markers in rats

Abstract: Ketogenic diets (KD) consist of high fat, moderate protein and low carbohydrates. Studies have suggested that KD may influence oxidative stress by affecting mitochondrial quantity and/or quality, and perhaps lengthen lifespan. Therefore, we determined the effects of KD on multi-organ mitochondria volume and oxidative stress markers in rats. Ten month-old male Fisher 344 rats (n = 8 per group) were provided with one of two isocaloric diets: standard chow (SC) or KD. Rats were euthanized if: a) vitality scores e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 37 publications
2
26
0
Order By: Relevance
“…Therefore, the relative muscle mass was higher in KD animals. This finding is consistent with earlier reports describing four-week ketogenic diet feeding [ 6 , 24 , 25 ]. Consequently, application of a ketogenic diet for four weeks is not harmful to muscle quantity.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Therefore, the relative muscle mass was higher in KD animals. This finding is consistent with earlier reports describing four-week ketogenic diet feeding [ 6 , 24 , 25 ]. Consequently, application of a ketogenic diet for four weeks is not harmful to muscle quantity.…”
Section: Discussionsupporting
confidence: 94%
“…Then the EDL muscle was removed, weighed, and frozen for subsequent analyses. For this study, EDL muscle was selected because it is a fast-twitch fiber muscle similar to the gastrocnemius and quadriceps femoris muscles, which have been used often in earlier ketogenic diet studies [ 22 , 24 26 ]. Also, EDL muscle is suitable to isolate with tendon-to-tendon manner for performing muscle contraction experiments.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to variable reports in exercise performance, some potential negative side effects, including increased adipose tissue mass [78,80], decreased muscle glycogen content [79], increased serum triglycerides [80], and decreased cardiac function [80], were noted. However, KDs may decrease mortality [81,82], improve memory [81], and increase muscle citrate synthase [82] in aged mice. Perhaps additional studies in animal models are necessary to help derive definitive conclusions.…”
Section: Ketogenic Diets and Exercise Performancementioning
confidence: 99%
“…This might be a limitation of the human study, and a well-designed in vivo or in vitro experiment may validate this result. It was reported that in an experiment that lasted for 762 days, muscle mitochondrial volume was increased by KD (Parry et al, 2018). Other authors show that a 12-week KD combined with daily treadmill exercise induced higher gene expression in markers of fatty acid oxidation, as compared with the control diet combined with exercise (Shimizu et al, 2018).…”
Section: Ketogenic Diet and Endurance Exercisementioning
confidence: 97%